The Opinion Of Mui Clerics In Banjarmasin City On The Sale And Purchase Of Virtual Property In The Online Game Growtopia - Ahmad Rizsky; Dr. Hj. Rabiatul Adawiyah, S.Ag, M.Ag; Fajrul Ilmi, S.Pd.I, M.Sy (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
This research is motivated by the rampant buying and selling of virtual property in the online game growtopia and considering the virtual property that is traded comes from online games. Of course, it can be said that the goods are not clear from the form that is not real, and there is no form or not physical, but only a virtual form, so that this is a problem among the community, especially for sellers and buyers. From the description of the problem above, the researcher conducted a study by asking the opinion of the ulama MUI Banjarmasin City with the intention of obtaining legal clarity regarding whether or not buying and selling virtual property in the online game growtopia if done. This type of research is field research using qualitative research approach, this is because the researcher conducts research directly to the field, by asking some questions to find out the opinion of MUI Ulama of Banjarmasin City regarding the sale and purchase of virtual property in growtopia online game and the ulama referred to here are ulama who are included in the field of fatwa, fatwa commission and economic empowerment commission of the people. The result of this research is first, from five opinions of MUI scholars in Banjarmasin City, it is known that four of the scholars allow buying and selling virtual property, because it has fulfilled all the pillars and conditions of buying and selling in Islam. One scholar does not allow the sale and purchase of virtual property, because it does not fulfill one of the requirements regarding the object in Islamic buying and selling. Second, the legal reasons that underlie the opinion of the MUI of Banjarmasin City include: because the original law of buying and selling is permissible, and basically all muamalah can be done, unless there is evidence that forbids it, then Allah SWT has legalized buying and selling and forbade usury. Furthermore, this sale and purchase has been based on mutual consent or mutual consent between the two parties. Such buying and selling must also not cause harm to oneself and must not cause harm to others. And basically everything that is beneficial is halal (permissible), as well as mutual harm (harm) is prohibited by Sharia guidance.